Selection of the best Average Normal Populations - Cieślik, Joachim; Sitek, Mirosława (Anthropological Review, 1987)
The work deals with the problem of choosing the best normal population in terms of the average. Two methods of choice are given depending on whether we are interested in choosing exactly one population or a subset including the best population. In both cases the probability of a correct decision P* depends on the amount of observations and the length of the confidence interval 6 for the highest mean. As regards the first method the length of the confidence interval & is fixed, whereas in the second method it is random. The method depends on whether the variances are known or not and whether they are identical or not. In the case of different and unknown variances only the two-stage method is allowed. The authors provide also an example illustrating the way of using both methods and tables of necessary critical values.